Embedment strength of Pinus sp. wood to metal pins - de Almeida, Diego Henrique; de Almeida, Tiago Hendrigo [UNESP]; Molina, Julio Cesar [UNESP]; Ferro, Fabiane Salles; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (Trans Tech Publications, 2014)
To know the physical and mechanical properties of wood to be employed as structural elements in is an important factor for its use in a rational way. The connections between members of timber structures are also relevant topic once local stress concentrations can occur and safety must be seriously taken in account. Brazilian Code ABNT NBR 7190: 1997 Design of Timber Structures provides guidelines for connections calculation based on two alternative limit states: wood strength to embedment or bending of the bolt. The purpose of this paper is estimate the strength to embedment of Pinus sp. to bolts in three directions with respect to the grain: parallel, perpendicular and inclined at 45°. Specimens obeying requirements of Brazilian Code related to bolts diameter (10mm) were prepared and tested. The embedment strength in parallel direction to the fiber was the highest and the failure modes were more frequent crushing and cleavage. © (2014) Trans Tech Publications, Switzerland.
Keywords: Embedment strength; Pinus sp; Timber structures; Wood; Wood properties